2009
DOI: 10.1016/j.fertnstert.2008.08.110
|View full text |Cite
|
Sign up to set email alerts
|

Variations in serum müllerian inhibiting substance between white, black, and Hispanic women

Abstract: Objective To compare serum mullerian inhibiting substance (MIS) levels between white, black and Hispanic women to determine if ovarian aging occurs at a different time course for women of different racial groups. Design Longitudinal study of serum MIS levels in women of different race/ethnicity over two different time points. Setting Women’s Interagency HIV Study, a multicenter prospective cohort study. Patient(s) Serum samples obtained from 809 participants (122 white, 462 black and 225 Hispanic women).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 25 publications
13
100
2
7
Order By: Relevance
“…To our knowledge, this is the first study to examine the association between BMI and AMH levels with direct correlations across different racial groups. First, we found no significant difference among AMH levels across all four racial groups, which is similar to findings reported by Freeman et al when examining comparing AMH levels between African-American and Caucasian women but conflicts with the findings of both Seifer et al and Bleil et al, which were expanded to also include Hispanic and Hispanic versus Asian women, respectively [22,25,26]. In addition, we found that age did have a significant negative correlation with both AMH levels and AFC across all races (p<0.05), which is consistent with previous findings [30][31][32][33].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To our knowledge, this is the first study to examine the association between BMI and AMH levels with direct correlations across different racial groups. First, we found no significant difference among AMH levels across all four racial groups, which is similar to findings reported by Freeman et al when examining comparing AMH levels between African-American and Caucasian women but conflicts with the findings of both Seifer et al and Bleil et al, which were expanded to also include Hispanic and Hispanic versus Asian women, respectively [22,25,26]. In addition, we found that age did have a significant negative correlation with both AMH levels and AFC across all races (p<0.05), which is consistent with previous findings [30][31][32][33].…”
Section: Discussionsupporting
confidence: 58%
“…Compared with Caucasian women, average AMH values were found to be decreased among African-American (25.2 %) and Hispanic (24.6 %) women after adjusting for age [25]. However, in another study, compared to Caucasian women, African-American women were shown to have lower AMH levels at younger ages (ages 25-30) but experience less of a reduction in AMH with advancing age, whereas Hispanic and Asian women between the ages of 25 and 45 have lower AMH levels [26].…”
Section: Introductionmentioning
confidence: 86%
“…Variability in the number of antral follicles may result in AMH level differences [18][19][20][21]. Recent studies indicate that AMH concentration may vary according to the ethnicity, with lower serum AMH level in African-American and Hispanic women in comparison to Caucasian women [22,23]. Through the menstrual cycle, AMH concentration seems to be relatively stable, although a slight increase is observed during the follicular phase of the regular menstrual cycle in women of age over 30 years [24].…”
Section: Discussionmentioning
confidence: 99%
“…Zwrócono również uwagę, że występują różnice w AMH zależne od pochodzenia etnicznego. U kobiet pochodzenia afro-amerykańskiego i hiszpań-skiego obserwowano niższe wartości w porównaniu z kobietami rasy kaukaskiej [22,23]. W cyklu stężenie AMH w surowicy krwi jest stałe, niezależnie od fazy [24].…”
Section: Implikacje Kliniczneunclassified
“…A pesar de que los estudios de corte transversal que han comparado las concentraciones de AMH en mujeres fumadoras y no fumadoras han arrojado resultados contradictorios, los estudios como el actual que han comparado estas concentraciones ajustando por edad han consistentemente encontrado que la declinación de AMH con la edad se acelera entre las fumadoras 16,17 .…”
Section: Discussionunclassified